DETERMINING A JUSTICE COLLABORATOR’S STATUS OF CORRUPTION: DISPARITIES CONSIDERATION OF INDONESIAN LAW ENFORCEMENT - Tofik Yanuar Candra; Joko Sriwidodo (Universitas Syiah Kuala, 2023)
The absence of a comprehensive legal framework for determining justice collaborator status in Indonesia has resulted in adverse consequences, particularly in the realm of corruption law enforcement, leading to discrepancies in its implementation. The objective of this study is to examine the process of identifying justice collaborators in Indonesia and assess the existing disparities in this determination. The present study employs a normative research design, wherein the author employs a descriptive qualitative approach. The existing literature indicates that the management of justice collaborators involved in corruption offenses within Indonesia's criminal justice system is currently governed by several Indonesian statutes, namely Acts Number 7 of 2006, Number 5 of 2009, Number 31 of 2014, and Circular Letter of the Supreme Court Number 4 of 2011. The presence of difficulties in the implementation of protecting Justice collaborators and the reluctance of the perpetrators to collaborate with law enforcement is evident in the disparity observed in the determination of justice collaborators in a corruption case in Indonesia.